Economic activities of forcibly displaced populations: An analysis of enterprises in Southern Bangladesh - Rosenbach, Gracie; Tiburcio, Ernesto; Filipski, Mateusz J.; Dorosh, Paul A.; Sen, Binayak (International Food Policy Research Institute, 2018)
Surveys of leaders in 45 communities and managers of 449 enterprises, conducted inside and around the camps for Forcibly Displaced Rohingyas in Cox’s Bazar, Bangladesh indicate substantial economic activity, mainly in the retail trade and services sectors. We find notable economic movement in and out of the camps by customers, hired workers, and businesses to purchase inputs. Rohingya adult male camp employment estimates converge in the range of 5.1%-6.2%, however hired Rohingya workers are systemically paid less than their Bangladeshi counterparts in nearly every sector. Regression analysis indicates that the sector of the enterprise and the education level of the owner of the enterprise are the main correlates of profitability and wage-bill inside the camps.